Improving quality standards of purchase policy and sustainable staple food safety - Cao, Chen; Shao, Kaichao (Frontiers in Sustainable Food Systems, 2024)
Food quality is closely related to food safety. Improving food quality, especially staple foods quality, is crucial to ensuring sustainable food safety. China's government is making efforts to improve the quality of staple foods and has improved quality standards of purchase policy for staple food. However, the actual effects of the new quality standards of purchase policy in implementation have not been verified. Based on this background, applying difference-in-differences models, this paper examines whether the new quality standards of purchase policy can improve the quality of staple food supply based on the wheat market transaction data. The results show that the new quality standard of purchase policy has a significant positive impact on the quality of staple food supply. The conclusion remains robust through several alternative tests. Further research shows that the new quality standards of purchase policy significantly expand the degree of quality premiums in the market, thereby improving the staple food supply quality. Our research provides an insight for policy or standard makers to change relevant purchase quality limits following consumer demand to ensure sustainable food security.